Fragility syndrome in elderly people - Paredes Núñez, Cynthia Lissette (2023)
Introduction: Frailty syndrome is a condition associated with growing old with high incidence in elderly people. Objective: To identify fragility syndrome in elderly people in the nursing home ''Sagrado Corazón de Jesús''. Methods: Descriptive, comparative, correlational and cross-sectional study. The total study population was 60 patients, the Fragility Tilburg Indicator (TFI) was used to measure total fragility, as well as each domain of fragility, including: physical fragility with 8 items, cognitive fragility with 4 items, and social fragility with 3 items. Results: Physical fragility has a mean of 2 points a maximum of 8 points with a mean of 6.8 points and a σ=1.55. Psychological fragility shows a minimum of 0 points a maximum of 4 points with a mean of 3.25 points and a σ=0.79. Social fragility shows a minimum of 0 points a maximum of 1 point with a mean of 0.9 points with a σ=3.0 points. Conclusions: Fragility is a complicated syndrome, which requires a special treatment because it is a frequent disorder in the elderly, so it is essential to perform a quick examination through the application of scales, in order to know the lifestyle, risk factors, and motor and mental skills that the elderly person has, so as to be able to interpret the management required by the patient.